BEHAVIOURAL RESPONSES OF AFRICAN CATFISH ( Clarias gariepinus BURCHELL, 1822) JUVENILES EXPOSED TO ACUTE CONCENTRATIONS OF BUTACHLOR (HERBICIDE) - Salim, A. M.; Dauda, A. B.; Yusuf, M. A. (FUDMA JOURNAL OF SCIENCES, 2021)
This study examined the behavioral changes induced by butachlor to the juveniles of Clarias gariepinus. The experiment consists of five treatments (0.6, 0.7, 0.8, 0.9 and 1.0 mg/l) and a control. Ten fishes were allotted in each test tank in duplicates. Observations on behavioral responses were made at 0, 12, 24, 48, 72 and 96 hours post-exposure. The opercular movement and tail fin beat rates were observed as counts per minute using a stopwatch. The behavioral patterns of the fish in the control group were normal, whereas in the exposed groups the fish tend to lose equilibrium and swim erratically with vigorous jerky movements. At the 12th and 24th hours the fish in the exposed groups showed hyper-active movement, but became hypoactive at the 48th hour. The mean values of the tail fin beat of the exposed groups were significantly higher (p<0.05) than that of the control at the 12th hour. At the 24th and 48th hour post-exposure the exposed groups showed significant (p<0.05) time-dependent decrease compared to the control. The tail fin beat became significantly higher (P<0.05) in the control group from 72nd hours onward. The decrease of tail fin beats at the 72nd and 96th hours were dose-dependent similar observations were also recorded in the opercular ventilation. At the 12th hour the opercular ventilation of the exposed fish was significantly higher (p<0.05) than the control whereas at the 24th and 48th hours, the opercular ventilation of the exposed groups showed a significant decrease (p<0.05) compared to the control.